Perancangan Media Informasi Tentang Gangguan â€Attention Deficit Hyperactivity Disorderâ€ (ADHD) pada Remaja - Alyssa Noor Afra; Aryoni Ananta (MAVIS : Jurnal Desain Komunikasi Visual, 2025)
This information media design aims to enhance teenagers' understanding of Attention Deficit Hyperactivity Disorder (ADHD) and reduce the negative stigma often associated with it. The media is presented as an educational animation tailored to the characteristics of young audiences aged 12–17, making it visually engaging, easy to understand, and communicative. The design process follows the 5W+1H method and consists of three main stages: briefing, design, and animation. The final output includes three informative videos titled “What is ADHD?”, “ADHD & Teenagers” and “Solutions for Late Diagnosis.” In addition to delivering essential information, this project encourages empathy among teens and provides guidance for recognizing early signs of ADHD. It is expected to raise awareness among teenagers, parents, and the broader community about the importance of timely diagnosis and proper treatment.